Turbulent kinetic energy dissipation rate and eddy diffusivity study in the tropical mesosphere using Jicamarca radar data - Guo, Liyu (2006)
The MST radar at Jicamarca Radar Observatory JRO is a powerful radar that can detect atmospheric turbulence on the Bragg scale of 3 m in the daytime mesosphere 60-85 km Since 2002 the radar was operated for a few days each year in the mode that collecting 1 minute Doppler spectra in four beam directions and 150 m resolution The spectral widths along with GSWM MSIS and SABER temperatures have been used to compute the kinetic energy dissipation rate due to atmospheric turbulence Eddy diffusivities K have also been calculated A small contamination due to beam broadening beam width 0 7 degree has been removed For most days median kinetic energy dissipation values of 1-10 mW kg increase with height consistent with the results from other VHF radars The variability during each day is large Turbulent dissipation rates and eddy diffusivities for individual layers and the day-to-day variability are discussed in relationship with the observed wind shear and estimated Richardson number.